Environmental nanopollutants : Sources, occurrence, analysis and fate - Szpunar, Joanna; Lamana-Jiménez, Javier (Croydon : Royal Society of Chemistry, 2023)
Nanopollutants are nanoparticles that have escaped into the environment and can include engineered nanoparticles as well as nanoparticles that are products of degradation (e.g. nanoplastics) or other processes. As many of these particles are only recently developed or described there is still a lot to learn about where they come from, where they end up and what risks they pose to health and the environment.
Includes references and index.
Keywords: Nanoparticles; Environmental chemistry; Nanoparticles Environmental aspects; Nanoplastics; Nanotechnology Environmental aspects